Palliative Care - Mollaoğlu, Mukadder (IntechOpen, 2019)
Palliative care is one of the most important factors in the fight against chronic diseases. It begins from the moment the patient is diagnosed, continues with curative treatment until death, and ends with care that supports the patient's family and other caregivers during the postmortem mourning process. In all these stages it is very important to improve the quality of life in patients, to relieve symptoms, and to support patients and their relatives in a dignified manner. This book includes basic information about palliative care, management of patient symptoms, support suggestions for psychological and social problems, needs of patients and their families, and how palliative care is handled in different countries. Written for healthcare professionals, students, and all interested readers, this book provides important information that can be used to improve the quality of life of patients as well as that of their families.